Sex differences in the therapy of kidney and ureteral stones. Issue 3 (May 2019) - Özsoy, Mehmet; Somani, Bhaskar; Seitz, Christian; Veser, Julian; Kallidonis, Panagiotis
Abstract : Purpose of review: Better understanding of sex differences affecting urolithiasis may help us offer tailored treatment strategies to our patients. Recent findings: The incidence of urolithiasis is increasing and the male-to-female ratio has decreased from 3 : 1 to 1.3 : 1 between 1970 and 2000. In women, obesity has a larger effect on the risk of developing urolithiasis [odds ratio (OR) 1.35; 95% confidence interval (CI): 1.33–1.37] compared with men (OR 1.04; 95% CI: 1.02–1.06). Urolithiasis is a risk factor for coronary artery disease in men (risk ratio = 1.23; 95% CI: 1.02–1.49) and for stroke in women (risk ratio = 1.12; 95% CI: 1.03–1.21). Women tolerate cystoscopic stent removal and shock wave lithotripsy better than men. For shock wave lithotripsy menopaused women have reported lower visual analog scale scores than menstruating women ( P < 0.001). Female sex was an independent predictor of stone impaction (OR 1.15; 95% CI: 1.03–1.27) and postoperative sepsis after ureteroscopy (OR 2.31; 95% CI: 1.14–4.37). Summary: The sex gap in urolithiasis is closing. The changing role of women in society and dietary habits can be responsible for this epidemiologic shift. Women show a higher threshold for pain during urologic procedures, but they suffer from infectious complications more than men. Urolithiasis is a risk factor for cardiovascular events in both sexes.